Abdullah Nasih Ulwan’s Philosophy of Islamic Education: A Critical Study of Its Relevance to Modern Educational Challenges - Husna, Sofiatul; Arif, Mahmud (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2025)
The contemporary landscape of education faces critical challenges marked by moral degradation, shifting social values, and the extensive influence of digital culture. These conditions demand a philosophical framework of Islamic education that is capable of responding holistically to the intellectual, spiritual, moral, and social needs of learners. This study critically examines Abdullah Nasih Ulwan’s philosophy of Islamic education and analyzes its relevance in addressing modern educational challenges. Using a qualitative approach and library research method, this study explores Ulwan’s fundamental educational concepts through textual analysis of his principal works—particularly Tarbiyat al-Aulad fi al-Islam—alongside contemporary academic publications. The findings show that Ulwan’s educational philosophy promotes a holistic and integrative framework covering objectives, curriculum, teaching methods, and the functional role of educational institutions, especially the family, school, and society. Moreover, Ulwan’s emphasis on moral and spiritual development, character formation, and parental responsibility demonstrates significant relevance for countering the negative impacts of globalization, digital exposure, and individualistic values. The study concludes that Ulwan’s philosophical perspective remains highly applicable to modern education when contextualized and adapted to contemporary pedagogical approaches. This research contributes theoretically by mapping Ulwan’s educational philosophy within the discourse of Islamic educational philosophy and practically by offering conceptual insights for the development of character-based Islamic education in the digital era.